Psychology and Consumer Culture: The Struggle for a Good Life in a Materialistic World. 2004
DOI: 10.1037/10658-008
|View full text |Cite
|
Sign up to set email alerts
|

Lethal consumption: Death-denying materialism.

Abstract: Modern man is drinking and drugging himself out of awareness, or he spends his time shopping, which is the same thing.-Ernest Becker, The Denied of Death Humans are by nature consumers. This book, although published on recycled paper, is a product of the consumption of trees; it is up to youthe reader-to decide whether the tome in its entirety, or this chapter in particular, is worth the timber or the energy used to recycle it. Yet, before we burden ourselves with too much lumbering guilt about that, we should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…It is also more reasonable to assume that motives engendered by personality bias people's beliefs about buying rather than If the sample had been drawn from a culture or subculture in which materialistic values were strongly condemned, it would be reasonable to predict a negative association between the motive to belong and materialism. But cultures that strongly and genuinely condemn materialistic lifestyles are probably hard to find (see Solomon, Greenberg, & Pyszczynski, 2004). the reverse (see McCrae & Costa, 1999, for insights about the relations between traits and beliefs).…”
Section: A Consideration Of the Model's Causal Assumptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also more reasonable to assume that motives engendered by personality bias people's beliefs about buying rather than If the sample had been drawn from a culture or subculture in which materialistic values were strongly condemned, it would be reasonable to predict a negative association between the motive to belong and materialism. But cultures that strongly and genuinely condemn materialistic lifestyles are probably hard to find (see Solomon, Greenberg, & Pyszczynski, 2004). the reverse (see McCrae & Costa, 1999, for insights about the relations between traits and beliefs).…”
Section: A Consideration Of the Model's Causal Assumptionsmentioning
confidence: 97%
“…If the sample had been drawn from a culture or subculture in which materialistic values were strongly condemned, it would be reasonable to predict a negative association between the motive to belong and materialism. But cultures that strongly and genuinely condemn materialistic lifestyles are probably hard to find (seeSolomon, Greenberg, & Pyszczynski, 2004).…”
mentioning
confidence: 99%
“…However, recent research demonstrated positive associations between reflections on death and increased materialistic tendencies (e.g., Kasser & Kasser, 2001). Moreover, both theoretical accounts (Arndt et al, 2004; Solomon, Greenberg, & Pyszczynski, 2004) and experimental research (e.g., Mandel & Heine, 1999) suggest that thoughts about death may heighten materialism and consequently increase products' appeal.…”
mentioning
confidence: 99%
“…In symbolic immortality, one imagines leaving a legacy or imprint that endures after one dies (Lifton, 1979). Symbolic denial is achieved through imagining that one lives on through one’s works, through the accumulation of power and wealth (Solomon, Greenberg, & Pyszczynski, 2004b), or through one’s children (Wisman & Goldenberg, 2005).…”
Section: Experiences That Either Trigger or Relieve Unconscious Deathmentioning
confidence: 99%